MYB8 Controls inducible phenolamide levels by activating three novel hydroxycinnamoyl-coenzyme a:polyamine transferases in nicotiana attenuata - Onkokesung, Nawaporn; Gaquerel, Emmanuel; Kotkar, Hemlata; Kaur, Harleen; Baldwin, Ian T.; Galis, Ivan (Plant Physiology, 2012)
A large number of plants accumulate N-acylated polyamines (phenolamides [PAs]) in response to biotic and/or abiotic stress conditions. In the native tobacco (Nicotiana attenuata), the accumulation of two major PAs, caffeoylputrescine and dicaffeoylspermidine (DCS), after herbivore attack is known to be controlled by a key transcription factor, MYB8. Using a broadly targeted metabolomics approach, we show that a much larger spectrum of PAs composed of hydroxycinnamic acids and two polyamines, putrescine and spermidine, is regulated by this transcription factor. We cloned several novel MYB8-regulated genes, annotated as putative acyltransferases, and analyzed their function. One of the novel acyltransferases (AT1) is shown to encode a hydroxycinnamoyl-coenzyme A: putrescine acyltransferase responsible for caffeoylputrescine biosynthesis in tobacco. Another gene (acyltransferase DH29), specific for spermidine conjugation, mediates the initial acylation step in DCS formation. Although this enzyme was not able to perform the second acylation toward DCS biosynthesis, another acyltransferase gene, CV86, proposed to act on monoacylated spermidines, was isolated and partially characterized. The activation of MYB8 in response to herbivore attack and associated signals required the activity of LIPOXYGENASE3, a gene involved in jasmonic acid (JA) biosynthesis in N. attenuata. These new results allow us to reconstruct a complete branch in JA signaling that defends N. attenuata plants against herbivores: JA via MYB8's transcriptional control of AT1 and DH29 genes controls the entire branch of PA biosynthesis, which allows N. attenuata to mount a chemically diverse (and likely efficient) defense shield against herbivores.

Silencing an N-acyltransferase-like involved in lignin biosynthesis in nicotiana attenuata dramatically alters herbivory-induced phenolamide metabolism - Gaquerel, Emmanuel; Kotkar, Hemlata; Onkokesung, Nawaporn; Galis, Ivan; Baldwin, Ian T. (Plos One, 2013)
In a transcriptomic screen of Manduca sexta-induced N-acyltransferases in leaves of Nicotiana attenuata, we identified an N-acyltransferase gene sharing a high similarity with the tobacco lignin-biosynthetic hydroxycinnamoyl-CoA: shikimate/quinate hydroxycinnamoyl transferase (HCT) gene whose expression is controlled by MYB8, a transcription factor that regulates the production of phenylpropanoid polyamine conjugates (phenolamides, PAs). To evaluate the involvement of this HCT-like gene in lignin production as well as the resulting crosstalk with PA metabolism during insect herbivory, we transiently silenced (by VIGs) the expression of this gene and performed non-targeted (UHPLC-ESI/TOF-MS) metabolomics analyses. In agreement with a conserved function of N. attenuata HCT-like in lignin biogenesis, HCT-silenced plants developed weak, soft stems with greatly reduced lignin contents. Metabolic profiling demonstrated large shifts (up to 12% deregulation in total extracted ions in insect-attacked leaves) due to a large diversion of activated coumaric acid units into the production of developmentally and herbivory-induced coumaroyl-containing PAs (N', N `'-dicoumaroylspermidine, N', N `'-coumaroylputrescine, etc) and to minor increases in the most abundant free phenolics (chlorogenic and cryptochlorogenic acids), all without altering the production of well characterized herbivory-responsive caffeoyl-and feruloyl-based putrescine and spermidine PAs. These data are consistent with a strong metabolic tension, exacerbated during herbivory, over the allocation of coumaroyl-CoA units among lignin and unusual coumaroyl-containing PAs, and rule out a role for HCT-LIKE in tuning the herbivory-induced accumulation of other PAs. Additionally, these results are consistent with a role for lignification as an induced anti-herbivore defense.